Psychological stress and its relationship to the psycho-social adjustment - Noureddine Ghafoor, Bushra (Opción, 2019)
The importance of the current study lies in finding the relationship between stress and social adjustment among university students by using Mulla Taher’s method for measuring psychological stress and Mahmoud’s method for measuring psycho-social adjustment. As a result, if the student fails to perform self-adjustment, this will cause psychological imbalance and increase the psychological stress, thus affecting his/her behavior and leads him/her to isolation from society. In conclusion, through the process of socialization performed by the family and the community, the individual acquires values, moral beliefs and different habits and attitudes.